SAT0483 Female sexual dysfunction in patients with systemic sclerosis. (12th June 2018) - Hermankova, B.; Spiritovic, M.; Smucrova, H.; Oreska, S.; Storkanova, H.; Pavelka, K.; Vencovsky, J.; Senolt, L.; Becvar, R.; Tomcik, M.
Abstract : Background: Systemic sclerosis (SSc) is a chronic autoimmune disease leading to various physical and psychological impairments including sexual dysfunction. Objectives: To assess sexual functions/quality of life and pelvic floor function in female SSc patients compared to age-/sex-matched healthy controls (HC), and to analyse the potential impact of disease activity, fatigue, physical activity and depression. Methods: In total, 41 women with SSc (mean age: 50.9, disease duration: 5.8 years, lcSSc/dcSSc: 18/23, mRSS: 13.6, ESSG activity index: 2.5), who fulfilled the ACR/EULAR 2013 criteria, and 41 healthy controls (mean age: 50.9) without rheumatic diseases filled in 12 well-established and validated questionnaires assessing sexual function/quality of life, pelvic floor function, fatigue, physical activity and depression. Full names of questionnaires are listed in the table 1. Data are presented as mean ±SEM. Results: Compared to HC, patients with SSc had significantly higher prevalence and greater severity of sexual dysfunction (FSFI, BISF-W: in all subscales as well as total scores), dysfunction of pelvic floor (PISQ-12, PFIQ7), and worse sexual quality of life (SQol-F) (table 1). Worse scores in SSc patients were associated with higher disease activity [ESSG activity index: SQol-F (r=−0.364, p=0.0443), PFIQ7-gynaecological subscale (r=0.492, p=0.0036)], greater fatigue [all three questionnaires FSS/FIS/MAF correlated negatively with FSFI, BISF-W], more severe depression [BDI-II: FSFI (r=−0.553, p=0.0002), BISF-W (r=−0.514, p=0.0007), PFIQ7 (r=0.495, p=0, 0010)], deteriorated quality of life [SHAQ: FSFI (r=−0.536, p=0.0003), BISF-W (r=−0.563, p=0.0001), SQol-F (r=−0.338, p=0.0382), PISQ-12 (r=0.563, p=0.0051), PFIQ7 (r=0.380, p=0.0142)], and worse ability to perform physical activities [HAP: FSFI (r=0.407, p=0.0082), BISF-W (r=0.409, p=0.0078)]. Conclusions: Women with SSc reported significantly impaired sexual function, sexual quality of life and pelvic floor function than age-matched healthy controls. Worse scores in SSc were associated with disease activity, physical activity, fatigue, depression and quality of life. Acknowledgements: Supported by AZV-16- 33574A and MHCR 023728. Disclosure of Interest: None declared